Fungal-induced programmed cell death - Williams,TJ; Gonzales-Huerta,LE; Armstrong-James,D (Journal of Fungi, 2021)
Fungal infections are a cause of morbidity in humans, and despite the availability of a range of antifungal treatments, the mortality rate remains unacceptably high. Although our knowledge of the interactions between pathogenic fungi and the host continues to grow, further research is still required to fully understand the mechanism underpinning fungal pathogenicity, which may provide new insights for the treatment of fungal disease. There is great interest regarding how microbes induce programmed cell death and what this means in terms of the immune response and resolution of infection as well as microbe-specific mechanisms that influence cell death pathways to aid in their survival and continued infection. Here, we discuss how programmed cell death is induced by fungi that commonly cause opportunistic infections, including Candida albicans, Aspergillus fumigatus, and Cryptococcus neoformans, the role of programmed cell death in fungal immunity, and how fungi manipulate these pathways.